Work-family balance and job satisfaction: the impact of family-friendly policies on attitudes of federal government employees - Saltzstein, Alan L.; Saltzstein, Grace Hall; Ting, Yuan (2001)
We use the 1991 Survey of Federal Government Employes to test a theoretical framework regarding the relationships between work and family demands, family-friendly policies, satisfaction with work-family balance, and job satisfaction for diverse groups of employees with different personal and family needs. We find that a variety of policies widely presumed to be "family friendly" were used to varying degrees by disparate groups of federal employees. The use of such policies had very diverse effects on both employee satisfaction with work-family balance and job satisfaction, within and across various groups of similarly situated employees. The assumptions underlying the provision of family-friendly policies and implications for the organization are examined. - Reproduced
Keywords: Job satisfaction; Civil service